INFLUENCE OF GLUCOSE ON SPECIFIC SURFACE AND TEXTURAL PROPERTIES OF NANO CRYSTAL MESOPOROUS ALUMINA - Obrenović, Z.; Gligorić, M.; Došić, A.; Damjanović, V. (Journal of Engineering & Processing Management, 2015)
Powders based on oxides and oxyhydroxides of aluminum, depending on their characteristics, have very diverse applications in various areas of the chemical industry. In recent years, obtaining powders with nano scale particle size, significantly expanding the possibilities for the application of this type of materials, especially in the field of so-called high technology with emphasis in the area of adsorbents. Mesoporous alumina is widely used as catalyst support and the adsorbent, and its physical properties, such as specific surface area, pore size distribution and total pore volume, has a significant impact on its efficiency in practice. Thermally activated powders of conventional intermediate γ-Al 2O 3, with a specific surface area (<300 m 2/ g), have limited catalytic application. The specific surface area of mesoporous alumina, obtained in the neutralization processes without additives, are generally in the range of 350-400 m 2 / g and have a wide distribution of pore size. Addition of glucose in these processes affect the obtaining mesoporous alumina with a large specific surface area and narrow pore distribution. For obtaining mesoporous alumina with a large specific surface area and narrow pore distribution in this work, it is used precipitation process of neutralization of aluminate ions with sulfuric acid with the addition of glucose. Powder X–ray diffraction (XRD), Fourier–transformed infrared spectroscopy (FT–IR) and low–temperature nitrogen absorption were used for characteration of transition phases and texture of synthesized and thermally activated samples.